Wising up through jazz and the metamorphosis of perception. (March 2023) - Holdaway, Marcelle
Abstract: Today's postnormal times marked by 'complexity, contradictions and chaos' require wisdom to heal ourselves and the planet. That wisdom is currently hidden, and a contribution to ignorance is epistemologies that are split into disciplinary silos. There has long been various theories and practices applied to 'expand' consciousness to access wisdom, and we draw upon one such practice that continues to be espoused by respected scholars today. Consequently, this paper argues for a pathway to wisdom that engages imagination and reveals alternative narratives through visual textual images that metaphors provide. The metaphor applied was jazz in its many expressions serving to 'paint a picture' of various disciplinary approaches in exploring potential perceptive and transformed knowledge systems. The critical futures research methodology, causal layered analysis (CLA) was applied to knowledges including mono-, multi-, inter-, trans and post disciplinarity. Mapping past, present and future led to a transformed future of radical new knowledges, the plausibility of which was examined through another futures methodology, the Futures Triangle. Potential pathways towards skills and knowledge-building were made visible through metaphor. This is but one pathway to consider in taking us beyond limited boundaries and ignorance towards unity and the wisdom so needed. Highlights: Our times are plagued by complex problems requiring pathways to uncover much needed wisdom. Applying visual images taps into the 'big picture' moving us towards a transformed future featuring radical new knowledges. Methodologies applied were critical futures tools Causal Layered Analysis (CLA) and the Futures Triangle. A series of jazz metaphors enabled the development of a transformative narrative. The plausibility of the new image was assessed by identifying barriers to the vision, pushes of the present and pulls of the future.